Purification of bacteriocins using size-exclusion chromatography - Bajpai, Vivek K.; Rather, Irfan A.; Hamad, Alshammari Fanar (Bangladesh Journal of Pharmacology, 2016)
The bacteriocin purification involves following main steps. a). Extraction of cell-free-supernatant of bacteria. b). Ammonium sulfate precipitation. c). Dialysis. d). Diafiltration using PVP and e). Size-exclusion chromatography. However, depending on the nature of work, the compound could be further analyzed by reverse-phase HPLC, NMR, mass spectrometry and sequencing. Video Clips of Methodology: Part 1: 4 min 52 sec Full Screen Alternate Part 2: 1 min 47 sec Full Screen Alternate